REVIVAL OF THE INDUSTRY OF THE KYRGYZ REPUBLIC AND OPPORTUNITIES FOR UNVEILING EXPORT POTENTIAL (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article discusses the current state of the industry in the Kyrgyz Republic, the dynamics of its recovery, and measures to unlock export potential. It highlights the main sectors with high export potential, key trade partners, and the role of institutional export support. Data from the International Trade Centre and national statistics are analyzed. The importance of digitalization, marketplaces, and government support measures is emphasized.
Keywords: industry, export, export potential, Kyrgyzstan, EAEU, processing